Molecular characterization of a carbon dioxide-dependent Escherichia coli small-colony variant isolated from blood cultures - Takehisa Matsumoto; Masayuki Hashimoto; Ching-Hao Teng; Po-Chuen Hsu; Yusuke Ota; Masaru Takamizawa; Ryosuke Kato; Tatsuya Negishi (Elsevier, 2020)
A carbon dioxide-dependent small-colony variant of Escherichia coli SH4888 was isolated from blood cultures of a patient with cholangitis. To date, little is known regarding the molecular mechanisms leading to formation of carbon dioxide-dependent phenotypes in clinical isolates, but abnormalities in the carbonic anhydrase are thought to cause carbon dioxide autotrophy. In this study DNA sequence analysis of the carbonic anhydrase-encoding can locus in the carbon dioxide-dependent E. coli SH4888 revealed that the isolate had a 325-bp deletion spanning from the 3'-terminal region of can to the 3'-terminal region of hpt, which encodes a hypoxanthine phosphoribosyltransferase. To confirm that the carbon dioxide-dependent SCV phenotype of E. coli SH4888 was due to the can mutation, we performed a complementation test with a plasmid carrying an intact can that restored the normal phenotype. However, E. coli SH4888 had increased virulence compared to the can-complemented E. coli SH4888 in a murine infection model. In conclusion, these data confirm that impaired carbonic anhydrase function can cause a carbon dioxide-dependent SCV phenotype in E. coli SH4888 and provides a fitness advantage in terms of infection.